Elemental Analysis of Asian Elephant (Elephas maximus) Teeth Using X-ray Fluorescence and a Comparison to Other Species - Nganvongpanit K. (2017)
© 2015, Springer Science+Business Media New York. Elemental composition in bone of the different species has variation depending on genetic and environmental factors especially their food habitat. The aims of this study were to conduct an elemental analysis of Asian elephant teeth, both deciduous (first molar, second molar, and tusk) and permanent (molar and tusk), and compare the elemental composition of permanent teeth among 15 species, mostly mammalian. These teeth were analyzed using X-ray fluorescence at two voltages: 15 and 50 kV. In Asian elephants, deciduous tusk showed a lower Ca/Zn ratio compared to permanent tusk, because of the lack of Zn in permanent molars. Ca/Fe ratio was higher in deciduous than permanent molars. For permanent teeth, elephant molars presented a high Ca/Pb ratio but no Ca/Zn, Ca/Sr, and Zn/Fe ratios because of the lack of Zn and Sr in the samples tested. The key elemental ratios for differentiating elephant deciduous and permanent tusk were Ca/P and Ca/Zn. The considerable variation in elemental ratio data across 15 species was observed. All tooth samples contained Ca and P, which was not surprising; however, Pb also was present in all samples and Cd in a large majority, suggesting exposure to environmental contaminants. From discriminant analysis, the combination of Ca/P+Ca/Zn+Ca/Pb+Ca/Fe+Ca/Sr+Zn/Fe can generate two equations that successfully classified six (dog, pig, goat, tapir, monkey, and elephant) out of 15 species at 100 % specificity. In conclusion, determining the elemental profile of teeth may serve as a tool to identify the tooth “type” of elephants and to potentially classify other species.